h(h+3)(h+1)=60

Simple and best practice solution for h(h+3)(h+1)=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h(h+3)(h+1)=60 equation:


Simplifying
h(h + 3)(h + 1) = 60

Reorder the terms:
h(3 + h)(h + 1) = 60

Reorder the terms:
h(3 + h)(1 + h) = 60

Multiply (3 + h) * (1 + h)
h(3(1 + h) + h(1 + h)) = 60
h((1 * 3 + h * 3) + h(1 + h)) = 60
h((3 + 3h) + h(1 + h)) = 60
h(3 + 3h + (1 * h + h * h)) = 60
h(3 + 3h + (1h + h2)) = 60

Combine like terms: 3h + 1h = 4h
h(3 + 4h + h2) = 60
(3 * h + 4h * h + h2 * h) = 60
(3h + 4h2 + h3) = 60

Solving
3h + 4h2 + h3 = 60

Solving for variable 'h'.

Reorder the terms:
-60 + 3h + 4h2 + h3 = 60 + -60

Combine like terms: 60 + -60 = 0
-60 + 3h + 4h2 + h3 = 0

The solution to this equation could not be determined.

See similar equations:

| y=log1/8x | | 2(p+3)+p+1=31 | | 6-8n+4n=30-92 | | (1/6)x3 | | 1/-8i | | 4x+5x=162 | | 3(4x-5)=6x+5 | | 2(2n-1)=(2n+7)+2 | | 3(2m-5)=11 | | 1222M+55=6 | | 0.6x+.3(40)=.5(x+40) | | 0.1a=0.001a | | A-55=-7 | | h(x)=-4.9x^2+5.7x+5 | | 2x^2+4y^2+4x-8y+200=0 | | 2(8+6)= | | a^2+a^2=5.64 | | 7(5x-7)-8=35x-57 | | sin(30-t)=0.5 | | 24=2(1)+2(t) | | x-5/4=x-9=3 | | 2x+4=2(x-4) | | 25+0.25times=40+0.25times | | x-0.15x=413.10 | | -9(x+6)+2=-3x-6(x+5) | | -2y-14=8y+16 | | 8+9(4x+6)=5-4(9x-6) | | 99/7x= | | (8x^2-6x-31)+(6x^2+9x)= | | -4/9*x=8 | | z/3-5/4 | | P(3≤x≤6)=P((3-3)/1.5≤z≤(6-3)/1.5) |

Equations solver categories